The language instinct : how the mind creates language - Pinker, Steven, 1954- (New York : Perennial Classics, 2000)
The codirector of the MIT Center for Cognitive Science explains how language works, how it differs from thought, why adults have difficulty learning foreign languages, and why computers cannot learn human language
TABLE OF CONTENTS --An instinct to acquire an ar t --Chatterboxes --Mentalese --How language works --Words, words, words --The sounds of silence --Talking heads --The tower of Babel --Baby born talking describes heaven --Language organs and grammar genes --The big bang --The language mavens --Mind design
Originally published: New York : W. Morrow and Company, ©1994
Includes bibliographical references (pages 469-502) and index
Keywords: Language and languages; Biolinguistics